The Influence of Motivation and Work Competence on Employee Performance: At A Company Engaged in Marketing - Toni Geopani; Asep Rochyadi Suherman; Adang Adang; Annita Jannah; Djadjat Suswanto (Majalah Bisnis & IPTEK, 2024)
This study investigates how work motivation and competency impact employee performance at a marketing-related organization. The research focused on work motivation and competence because these factors are critical in determining an individual's success within the organization's framework. The regression analysis method examines Employee performance in connection to these variables. Based on the research findings, motivation has a total influence of 40.7% on employee performance, making it the most significant factor. Motivation is an innate desire that propels people to accomplish the objectives they set for themselves at work. A high level of motivation can boost workers' morale, commitment, and work ethic. Managers must comprehend and use the elements that inspire workers, such as rewards for accomplishments, chances for professional growth, and suitable incentives. However, with a total influence of 27.3%, work competency also has a noteworthy impact on employee performance. Job competencies are the set of abilities, attitudes, and knowledge required to succeed in a specific work. Workers with solid work abilities are typically better equipped to perform their jobs quickly and effectively. As a result, the organization's management must be dedicated to enhancing worker competency through development, training, and ongoing education. With a coefficient of determination value of 68.1%, the analysis demonstrates that the influence of both job competence and motivation significantly influences variations in employee performance. Nonetheless, these two factors account for just about 31.9% of the variability in performance. External variables like the workplace, organizational policy, external economic situations, and internal employee considerations may also impact employee performance. These results give the organization's management helpful information for creating plans and policies that enhance worker performance. Enhancing work competence and staff motivation can be a significant starting point. To improve effectiveness, businesses must also consider other aspects affecting employee performance. The study highlights the significance of work motivation and competence as critical elements influencing employee performance in a marketing-related organization. Enterprises are expected to enhance their total performance, production, and efficiency by comprehending and controlling these aspects. To improve knowledge of the variables affecting worker performance and to pinpoint more targeted approaches to boosting competence and motivation at work, further study can be done.